Warum Abwehrmaßnahmen gegen Übernahmen in Spanien? - Margalida Alemany; Rafel Crespi-Cladera (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The adoption of takeover protections, from the empirical side, has been focused to find supporting evidence to the entrenchment hypothesis or to the shareholder value hypothesis. The expected result is a negative impact on shareholder wealth when decisions for additional takeover defenses are taken. Alternatively, external control gives more negotiation power, allowing for higher takeover prices, which is expected to increase shareholders' wealth. These two hypotheses have been widely tested in the US and the UK, where the market for corporate control is active, however they gained little attention in continental Europe. Our research, based on a sample of Spanish listed companies, reports several types of takeover protections, some of them, like voting caps, are very strong. The underlying question of the paper is about the reason why companies protect themselves against takeover and about the impact on shareholder's returns. Using the event study methodology, our results support the existence of a significant wealth effect, measured by an abnormal return of 0.5%, at the date of adoption, although the cumulative abnormal return for a [-8, +4] window is negative and significant. These inconclusive results reinforce the evidence that protections have been adopted by companies in a growing economic context. Effectively the companies of the sample outperform market and industry stock returns. Additional explanations of the significance of abnormal returns like stock trade volume,
Keywords: 330; Übernahme; Börsenkurs; Shareholder Value; Corporate Governance; Spanien